Eat your vegetables : bold recipes for the single cook - Yonan, Joe (Ten Speed Press, 2013)
"A collection of eclectic vegetarian and vegan recipes for singles as well as lone vegetarians in meat-eating households, from the beloved Washington Post editor and author of Serve Yourself. An increasing number of Americans are turning to plant-based diets, both for their health and the economic benefits. And for many, they are the only one in their household who has made the change--making it the perfect time for this book of vegetarian, flexitarian, and vegan recipes specifically sized for single portions. In addition to 80 delectable and satisfying recipes, Eat Your Vegetables features essays on moving beyond mock meat and the evolution of vegetarian restaurants, as well as economical tips for shopping for, storing, and reusing ingredients"--Provided by publisher.